The therapeutic effect of traditional Chinese medicine on breast cancer through modulation of the Wnt/β-catenin signaling pathway - Li, Hongkun; Li, Jiawei; Zhang, Yifan; Zhao, Chengcheng; Ge, Jun; Sun, Yujiao; Fu, Hui; Li, Yingpeng (Frontiers in Pharmacology, 2024)
Breast cancer, the most prevalent malignant tumor among women globally, is significantly influenced by the Wnt/β-catenin signaling pathway, which plays a crucial role in its initiation and progression. While conventional chemotherapy, the standard clinical treatment, suffers from significant drawbacks like severe side effects, high toxicity, and limited prognostic efficacy, Traditional Chinese Medicine (TCM) provides a promising alternative. TCM employs a multi-targeted therapeutic approach, which results in fewer side effects and offers a high potential for effective treatment. This paper presents a detailed analysis of the therapeutic impacts of TCM on various subtypes of breast cancer, focusing on its interaction with the Wnt/β-catenin signaling pathway. Additionally, it explores the effectiveness of both monomeric and compound forms of TCM in the management of breast cancer. We also discuss the potential of establishing biomarkers for breast cancer treatment based on key proteins within the Wnt/β-catenin signaling pathway. Our aim is to offer new insights into the prevention and treatment of breast cancer and to contribute to the standardization of TCM.